Low-gluten altar bread and mustum: Canons 924 and 29-34 - Provost, James H. (Roman replies and CLSA advisory opinions 1995, 1995)
On June 19, 1995 Cardinal Ratzinger sent a two-page letter to the heads of episcopal conferencces, communicating the results of a June 22, 1994 ordinary meeting of the Congregation for the Doctrine of the Faith. The letter deals with the use of low-gluten altar breads and mustum as matter for the celebration of the Eucharist. What is the force of this letter canonically, and does it establish a new impediment to orders?